Occupational risk deriving from mycotoxin contaminated environment: an update - Viegas, Susana (2017)
Occupational exposures to mycotoxins are supposed to be very frequent but rarely reported in the scientific literature. Exposure to mycotoxins was shown in animal production and food processing sectors confirming that occupational exposure can be non-negligible. It is of extreme importance to characterize the mycotoxins exposure: identify the mycotoxins related to each setting; concentration; duration; factors that may influence the exposure. Extensive search was performed to identify scientific papers, available in different scientific databases (PubMed and Web of Science). Fifteen papers were found between the years of 1981 and 2017 reporting occupational exposure to mycotoxins. After 2000 the number of papers increased and the focus changed from studying one mycotoxin to several mycotoxins in the same sample. All the studies demonstrated the presence of mycotoxins in workplace environments and that there was the possibility of the workers being exposed to mycotoxins through inhalation.